2008
DOI: 10.1111/j.1365-2141.2008.07269.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing and treating Diamond Blackfan anaemia: results of an international clinical consensus conference

Abstract: SummaryDiamond Blackfan anaemia (DBA) is a rare, genetically and clinically heterogeneous, inherited red cell aplasia. Classical DBA affects about seven per million live births and presents during the first year of life. However, as mutated genes have been discovered in DBA, non-classical cases with less distinct phenotypes are being described in adults as well as children. In caring for these patients it is often difficult to have a clear understanding of the treatment options and their outcomes because of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
577
1
51

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 421 publications
(640 citation statements)
references
References 130 publications
(209 reference statements)
11
577
1
51
Order By: Relevance
“…Diamond Blackfan anemia (DBA) is a rare, congenital anemia often diagnosed by one year of age[1]. Patients with DBA have a block in erythropoiesis, and often have craniofacial anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Diamond Blackfan anemia (DBA) is a rare, congenital anemia often diagnosed by one year of age[1]. Patients with DBA have a block in erythropoiesis, and often have craniofacial anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…In their timely review, Vlachos et al (2008) provided a nuanced picture of the challenges involved in the diagnosis of DiamondBlackfan Anaemia (DBA) and touched on 'non-classical' cases. Arguably, from a diagnostic viewpoint these particular instances are of greatest relevance to most haematologists and we believe the topic deserves greater emphasis.…”
mentioning
confidence: 99%
“…In spite of her age, absent overt family history and a pancytopenic presentation, our patient's relatively well preserved marrow cellularity, macrocytosis and a hypothenar flexion deformity prompted us to consider evaluation for DBA. Measurement of eADA is considered a reasonably reliable indicator of DBA and a minor diagnostic criterion in DBA (Orfali et al, 2004;Vlachos et al, 2008), whereas the incidence of eADA elevation in severe aplastic anaemia (SAA) has not been studied to date. In addition to the unusual presentation of non-classical DBA in a young adult, this case is distinguished by progressive pancytopenia (not currently considered a diagnostic criteria for DBA; Diamond et al, 1976) that, unlike reported cases of trilineage haematopoietic defects in DBA, preceded treatment, (Giri et al, 2000).…”
mentioning
confidence: 99%
“…< d'une greffe qui, en France, est proposée dans les formes graves dépendantes de transfusions, ou les formes compliquées. Un article de consensus sur le diagnostic et le traitement de l'ADB a été récemment publié par une communauté internationale de cliniciens [7]. L'ADB est liée à un défaut intrinsèque des progéniteurs érythroïdes et non pas du stroma médullaire, comme l'indiquent à la fois des données in vitro et le succès curatif des greffes de moelle.…”
Section: L'anémie De Diamond-blackfanunclassified
“…La cartographie pangénomique des SNP (single nucleotide polymorphisms) réalisée dans 215 familles a révélé d'autres locus en lien avec l'ADB : une région de 18 Mb sur le chromosome 8 (8p23. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] et des régions plus petites sur les chromosomes 6 et 10. Concernant le chromosome 10, le séquençage du gène codant la protéine ribosomique RPS24 a mis en évidence chez trois patients deux mutations non-sens et une délétion de la région codante, absentes lors de l'analyse de 200 génomes contrôles [15].…”
Section: L'adb Est Associée à Des Mutations Dans Des Protéines Ribosounclassified